Designing and developing an accessible web-based assistive technology for students with visual impairment. - Kamalı-Arslantaş, Tuğba; Yıldırım, Soner; Altunay, Banu (Assistive Technology, 2023)
This article introduces the design principles of a web-based assistive technology (WAT) developed for students with visual impairment (VI). The pedagogical goal guiding the development process was the enhancement of vocabulary knowledge for students studying English as a foreign language (EFL) in terms of their spelling and semantics. The study attempted to overcome the problems of individuals with VI through provision of an accessible and suitable learning environment. A design-based research (DBR) framework with a qualitative approach was employed with three groups of participants (students, experts, and families). The study's results revealed important findings for researchers, educators, and teachers of students with VI. The qualitative data analysis revealed that the WAT was accurate, appropriate, and accessible, especially in underlining design considerations. An appropriate set of distinct design principles that were founded based on the particular learning context of the study were also produced.